Revised Guidelines for Public Debt Management. (Manuals and Guides, 2015)
The Revised Guidelines for Public Debt Management have been developed as part of a broader work program undertaken by the IMF and the World Bank to strengthen the international financial architecture, promote policies and practices that contribute to financial stability and transparency, and reduce countries external vulnerabilities.